Utilization of rice-straw as livestock feed - Bakshi, M. P. S.; Wadhwa, M. (Indian Farming, 2018)
The rice-straw fermented with urea in stacks or bales or used in complete feed blocks, has great potential as livestock feed. The use of rice-straw in this way can both contribute to the food basket and avoid environmental problems that arise from the current practice of burning rice straw.